Heart transplantation experiences: a phenomenological approach - Araujo Sadala, Maria Lucia [UNESP]; Groppo Stolf, Noedir Antonio (Wiley-Blackwell, 2008)
Aim. The aim of this study was to understand the heart transplantation experience based on patients' descriptions.Background. To patients with heart failure, heart transplantation represents a possibility to survive and improve their quality of life. Studies have shown that more quality of life is related to patients' increasing awareness and participation in the work of the healthcare team in the post-transplantation period. Deficient relationships between patients and healthcare providers result in lower compliance with the postoperative regimen.Method. A phenomenological approach was used to interview 26 patients who were heart transplant recipients. Patients were interviewed individually and asked this single question: What does the experience of being heart transplanted mean? Participants' descriptions were analysed using phenomenological reduction, analysis and interpretation.Results. Three categories emerged from data analysis: (i) the time lived by the heart recipient; (ii) donors, family and caregivers and (iii) reflections on the experience lived. Living after heart transplant means living in a complex situation: recipients are confronted with lifelong immunosuppressive therapy associated with many side-effects. Some felt healthy whereas others reported persistence of complications as well as the onset of other pathologies. However, all participants celebrated an improvement in quality of life. Health caregivers, their social and family support had been essential for their struggle. Participants realised that life after heart transplantation was a continuing process demanding support and structured follow-up for the rest of their lives.Conclusion. The findings suggest that each individual has unique experiences of the heart transplantation process. To go on living participants had to accept changes and adapt: to the organ change, to complications resulting from rejection of the organ, to lots of pills and food restrictions.Relevance to clinical practice. Stimulating a heart transplant patients spontaneous expression about what they are experiencing and granting them the actual status of the main character in their own story is important to their care.
Keywords: chronic illness; heart transplantation; nurses; nursing care; patients' lived experience; phenomenology